2017
DOI: 10.3855/jidc.9339
|View full text |Cite
|
Sign up to set email alerts
|

Serologic evidence and risk factors for Helicobacter pylori infection in animals and humans

Abstract: Introduction: Helicobacter pylori (H. pylori) is one of the most common bacterial infections among humans worldwide. Although many records imply its interfamilial acquisition, the role of animals remains poorly understood. This study was undertaken to investigate the seroprevalence of H. pylori in animals and their human contacts in Cairo and Giza governorates, Egypt. Methodology: Commercial enzyme-linked immunosorbent assay (ELISA) kits were used to detect IgG antibodies to H. pylori in dogs, cattle, and huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
1
10
0
2
Order By: Relevance
“…The prevalence of H . pylori was 29.4%, which is similar to that reported in other studies (19, 21, 27%) 6 , 33 , 34 . Comparing the occurrence of H .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The prevalence of H . pylori was 29.4%, which is similar to that reported in other studies (19, 21, 27%) 6 , 33 , 34 . Comparing the occurrence of H .…”
Section: Discussionsupporting
confidence: 90%
“…We demonstrated recently a high sero-prevalence of H . pylori in humans having contact with animals 6 . Additionally, other studies reported that people that have direct contact with farm animals such as abattoir workers 30 and shepherds 31 , 32 have a high prevalence of H .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of helicobacter was investigated in 290 patients from Macau, China [40]. In Egypt, serological detection of H. pylori was done by [27] in dog and human revealed that 37.2% (35/94), 44.4% (40/90) respectively was positive. Twenty -nine serum samples which taken from owners of infected dog revealed 51.7% were found to have antibodies to H. pylori.…”
Section: Discussionmentioning
confidence: 99%